Estimates of maternal mortality worldwide between 1990 and 2005: an assessment of available data - Hill, Kenneth; Thomas, Kevin; AbouZahr, Carla; Walker, Neff; Say, Lale; Inoue, Mie; Suzuki, Emi (The Lancet (British edition), 2007)
Maternal mortality, as a largely avoidable cause of death, is an important focus of international development efforts, and a target for Millennium Development Goal (MDG) 5. However, data weaknesses have made monitoring progress problematic. In 2006, a new maternal mortality working group was established to develop improved estimation methods and make new estimates of maternal mortality for 2005, and to analyse trends in maternal mortality since 1990. We developed and used a range of methods, depending on the type of data available, to produce comparable country, regional, and global estimates of maternal mortality ratios for 2005 and to assess trends between 1990 and 2005. We estimate that there were 535 900 maternal deaths in 2005, corresponding to a maternal mortality ratio of 402 (uncertainty bounds 216–654) deaths per 100 000 livebirths. Most maternal deaths in 2005 were concentrated in sub-Saharan Africa (270 500, 50%) and Asia (240 600, 45%). For all countries with data, there was a decrease of 2·5% per year in the maternal mortality ratio between 1990 and 2005 (p<0·0001); however, there was no evidence of a significant reduction in maternal mortality ratios in sub-Saharan Africa in the same period. Although some regions have shown some progress since 1990 in reducing maternal deaths, maternal mortality ratios in sub-Saharan Africa have remained very high, with little evidence of improvement in the past 15 years. To achieve MDG5 targets by 2015 will require sustained and urgent emphasis on improved pregnancy and delivery care throughout the developing world.